UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM-BASED LEARNING - Isnawati, Rahmah; Fatmiyati, Novita; Hartini, Sri (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2024)
This research aims to improve the mathematics learning outcomes of seventh-grade students in SMP Negeri 2 Polokarto for the academic year 2022/2023 through the implementation of Problem-Based Learning (PBL) model. The study involved 23 students from class VII A of SMP Negeri 2 Polokarto for the academic year 2022/2023, using a Classroom Action Research (CAR) method conducted over 2 cycles, with each cycle consisting of 1 session. Each cycle consisted of 4 stages: planning, action, observation, and reflection. Data was collected through evaluation tests conducted at the end of each cycle and analyzed descriptively and quantitatively (by calculating the average scores and students' learning mastery) to compare the results between cycles and observe any improvements. From the data analysis conducted, it was found that the implementation of the Problem-Based Learning model could enhance students' learning outcomes. This is evident from the average learning outcomes of students in cycle 1, which were 69.65, with a percentage of students who achieved the Minimum Completion Criteria (KKM) being 56.5%, and the average learning outcomes of students in cycle 2, which were 82.78, with a percentage of students who achieved the KKM being 82.6%. There was an increase in the average learning outcomes and the percentage of students who achieved the KKM.